The devil's diary : Alfred Rosenberg and the stolen secrets of the Third Reich - Wittman, Robert K. (New York, NY : William Collins, 2016)
An unprecedented, page-turning narrative of the Nazi rise to power, the Holocaust, and Hitler's post-invasion plans for Russia told through the recently discovered lost diary of Alfred Rosenberg - Hitler's `philosopher' and architect of Nazi ideology
Includes bibliographical references (pages [485]-494) and index
Keywords: Hitler, Adolf , -- 1889-1945 -- Friends and associates; Rosenberg, Alfred , -- 1893-1946 -- Diaries; National socialism -- Philosophy; Nazis -- Diaries